Oral amoxicillin challenge for low‐risk penicillin allergic patients. Issue 2 (12th January 2022) - Livirya, Silabhakta; Pithie, Alan; Chua, Ignatius; Hamilton, Niall; Doogue, Matthew; Isenman, Heather
Abstract: Background: Penicillin allergy is the most reported adverse drug reaction (ADR). Being labelled with 'penicillin allergy' is associated with suboptimal antibiotic therapy and poor patient outcomes. Most labelled with 'penicillin allergy' are at low risk of harm from penicillins and guidelines recommend testing for accurate diagnosis. Although skin testing is recommended to exclude immunoglobulin E (IgE)‐mediated reactions, there is limited access in most settings. Aims: To evaluate oral amoxicillin challenge without prior skin testing for patients labelled with 'penicillin allergy' assessed as low risk during hospital admission. Methods: General Medical inpatients with a 'penicillin allergy' label were assessed. For those who had tolerated a penicillin since the index event, the ADR label was removed. Those assessed as 'low risk' were administered 250 mg amoxicillin orally without prior skin testing. The durability of de‐labelling was subsequently assessed by review of clinical records. Results: Of 224 patients with a history of a penicillin ADR, 162 (72%) were low risk. A further 12 were excluded and of the remaining 150, 56 (37%) had tolerated penicillins since their index reaction and were de‐labelled without challenge, 15 (10%) with a non‐allergic history were de‐labelled. The remaining 79 were offered an oral amoxicillin challenge; 38 declined and 41 tolerated amoxicillin. Overall, 112 of the 224 (50%) patients had their ADR label removed. Conclusions: A careful ADR history enables de‐labelling of many patients. An oral amoxicillin challenge without prior skin testing is safe and feasible for low‐risk penicillin allergic patients while in hospital.